A new approach for near real-time micro-CHP management in the context of power system imbalances – A case study. (1st January 2015) - Zapata Riveros, J.; Donceel, R.; Van Engeland, J.; D'haeseleer, W.
Highlights: An aggregator consisting of micro-CHPs was proposed. A near-real time balance optimization was developed. A case study that resembles the actual situation of the Belgian energy market is studied. Using the near-real time balance optimization a cost decrease between 2.5% and 5% can be achieved. Abstract: In order to ensure reliable operation of the electric grid, it is required to keep the balance between total generation and consumption of power in real-time. This task is performed by the transmission system operator. Nowadays, with the large penetration of intermittent generation on the electric grid there is a need to increase the flexibility of the system in order to ensure the balance. The present study develops a methodology to provide near real-time balancing services making use of an aggregation of micro-CHP devices. The controller of the aggregator bids electricity into the day-ahead market using the expected heat demand and spot market prices. The main focus of this work is on the near real-time optimization which is performed during the actual day. This optimization provides the opportunity to obtain extra profits by rescheduling the operation of the aggregator. The rescheduling is done in order to compensate the total system imbalance. To achieve this, every time step, the aggregator evaluates the system demand for up or down regulation and decides if it is profitable to adjust its position to provide balancing services to the power system. The methodology is applied to a case study that resembles the actual situation of the energy market and CHP installations in Belgium. The results show that using the near real-time balancing optimization a total cost decrease of 5% can be achieved depending on the season. This conclusion is valid even if there is an increase of the gas prices and if the actual governmental support on CHPs is not taken into account.